Estrategia Óptima de Corta de Nivel de Rodal en Plantaciones de Pinus radiata - Meneses, Mario; Olivares, Benjamín (Bosque (Valdivia), 1986)
A dynami c programming mode l for thinning s an d harvest in Pinus radiata D. D o n in presented. Stat e vector for various thinning s regimes is obtained from the RADIAT A simulator which also controls t h e dynamic s of th e mode l an d generates t h e basic network. The model potentiality is illustrated with an exampl e which only considers physical variables in the objective function